The impact of technological innovations on money and financial markets - Jan A. Kregel; Paolo Savona (Levy Economics Institute of Bard College, 2020)
According to Senior Scholar Jan Kregel and Paolo Savona, attempting to maintain the status quo in the face of the introduction of some recent technological innovations-chiefly cryptocurrencies and associated instruments based on distributed ledger technology, the deployment of artificial intelligence, and the use of data science in financial markets-will create risks that increase instability and threaten national financial systems. In this policy brief, they analyze the impacts of these innovations on the present institutional environment and outline an appropriate regulatory framework. Kregel and Savona argue that a public monopoly on the issuance of cryptocurrency could promote financial stability and help repair the dissociation between finance and the real economy.
Keywords: 330; Technischer Fortschritt; Geldmarkt; Finanzmarkt; Virtuelle Währung